Applications of nanocellulose as biosensing platforms for the detection of functional biomacromolecules: A Review - Hashem, Abu; Ibrahim Khalil,; Mohammad Al Mamun,; Md. Shalauddin,; M. A. Motalib Hossain,; Ab Rahman, Marlinda; Simarani, Khanom; Johan, Mohd Rafie (Malaysian NANO-An International Journal, 2022)
Cellulose is a group of materials that can be made into low-cost devices because they are the most common biomaterials in nature. Cellulose-based polymers are flexible, biocompatible, biodegradable, and easy to functionalise and mass produce. Cellulosic substrates are attractive biosensing platforms because of their unique properties, exceptional simplicity, and compatibility with standard technologies. Furthermore, cellulose-based biosensing approaches can meet the following criteria for optimal diagnostic assays or devices: real-time connectivity; simplicity of specimen collection; affordability; specificity; sensitivity; user-friendliness; speed and robustness; and deliverability to end-users. As a result, cellulose is suitable for constructing novel analytical devices in the biosensing community. The use of cellulose as a nano-engineered matrix material has enabled recent advancements in biosensors. Several methodologies for producing cellulose-based composites for the fabrication of various biosensors have been described and reviewed. Biological macromolecules have immense importance in genetic and pathogenicity detection. Likewise, there are many research reports, but there is a gap regarding review in this area of biological macromolecule detection like nucleic acids and proteins. This study looked at this previously unexplored area as well as the unique features that make it a good choice for biosensing applications and the engineering features of cellulose-based biosensors. It also looked at how different analytical systems have used such matrices to detect biological macromolecules (DNA, proteins, and RNA) in different samples.